ORALITY AS THE REPRESENTATION OF MADNESS IN THE POEM HOWL BY ALLEN GINSBERG - Randy Ridwansyah (Humaniora, 2013)
This paper examines the characteristics of orality as the representation of madness in the poem Howl by Allen Ginsberg. Orality and madness are two major aspects of Beat literary tradition. The characteristics of orally based thought and expressions as proposed by Ong are found in the poem and have significance to the theme of madness in the poem. Madness is manifested not only in content, but also in the form of poetic structure of the poem.It was found that textual orality in Howl serves to represent the effect of mind and body alteration caused by drug-induced madness on the perception of reality. Drug-induced madness both accelerates and decelerates the speaker’s perception in the poem, which is shown in the speech pattern of the narrative. All the perceptions captured by the mind and all the sensations felt by the senses take place almost simultaneously and are verbally manifested as they are into written language. This results in incoherent and ungrammatical sentences creating chaos, a form of language madness.